Journal of East Asian Studies.
Covers scholarly studies on Southeast Asian countries such as: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, East Timor, Singapore, Thailand and Vietnam. Publishes articles from a wide range of disciplines in the humanities and social sciences including economics.